The Influences of Motivation, Opportunity and Ability on Customer to Customer Online Know-How Exchange and Social Identity as a moderator in Indonesian Z Generation - Nugrahani Machali, Rahutami; Abdul Wahid, Nabsiah (International Journal of Engineering and Technology, 2018)
This study examines the influences of motivation, opportunity, and ability on customer to customer online know-how exchange and social identity as a moderator in Indonesian Z generation. This study focuses on the behavior of Indonesian Z generation. The study is designed to be quantitative in nature. The causal relationship between variables will be investigated via an online questionnaire that will be distributed to Indonesian Z generation.Â Â